ANALOGUE MODELLING OF THE INFLUENCE OF SHAPE AND PARTICLE/MATRIX INTERFACE LUBRICATION ON THE ROTATIONAL BEHAVIOUR OF RIGID PARTICLES IN SIMPLE SHEAR - Ceriani S.; Mancktelow N.S.; Pennacchioni G. (My University, 2003)
The rotational behaviour of a rigid particle embedded in a linear viscous matrix undergoing cylindrical simple shear (Couette) flow was studied in 2D rock-analogue experiments. The influence of particle shape (elliptical vs. monoclinic), aspect ratio and the nature of the matrix/particle interface (lubricated vs. unlubricated) was investigated. Both matrix (PDMS) and lubricant (liquid soap) were linear viscous, with a viscosity ratio of ca. 104. Without lubricant, the rotational behaviour of all particles closely approximates the Jeffery theory. Lubricated monoclinic particles with the long diagonal initially parallel to the shear direction show back rotation and approach a stable position. Lubricated elliptical particles initially parallel to the shear direction also show back rotation but only transiently stabilize. Weak planar zones in the matrix adjacent to unlubricated elliptical particles do not induce backward rotation. In general for elliptical particles, rotation rate as a function of orientation depends on axial ratio and thickness of the lubricant mantle. For thick mantles (initially >10% of the volume of the particle), rotation rates are faster than Jeffery theory. For very thin mantles they are markedly slower compared with thick mantles, particularly when the long axis is nearly parallel to the shear direction. Rotation rates are never strictly zero, so true stabilization does not occur. However, for more elongate particles (axial ratio=6) rotation rates are so slow that a very strong shape preferred orientation would develop in a lubricated elliptical particle population. In experiments, the volume of lubricant is constant and the thickness adjacent to the long side of the particle progressively decreases with increasing strain. In natural examples of porphyroclast systems, the weak mantle continually develops by recrystallization and/or cataclasis of the rigid clast core and a steady state between production and thinning could be attained, potentially leading to true stabilization for particles with a high axial ratio.
Keywords: ANALOGUE MODELLING; RIGID PARTICLES; PORPHYROCLASTS; ROTATION; STABILIZATION; SHEAR ZONES